Food insecurity, inflation and government aid: Evidence from a household survey in developing Asia - Peter J. Morgan; Angelica Maddawin; Dina Azhgaliyeva; Wataru Kodama; Long Quang Trinh (Asian Development Bank Institute (ADBI), 2024)
Food insecurity has become of increasing concern following the economic downturn during the COVID-19 pandemic and the subsequent sharp rise in inflation, including food price inflation. To better understand the conditions of food insecurity and the impacts of inflation and other drivers of food insecurity in developing Asia, we carried out a household survey in 2023 in seven countries in Southeast Asia and nine countries in the Caucasus and Central Asia. The key results are as follows. First, households that had low income and experienced income declines and/or financial difficulties were more likely to experience food insecurity. Second, households that experienced high inflation, including food price inflation, also tended to have higher food insecurity. Third, among the coping strategies adopted by households, only applying for government aid had a significant effect on reducing food insecurity. Our study contributes to the literature because of both the large number of countries and the large number of variables covered in the analysis. These results highlight the need to develop effective measures to reduce food insecurity among vulnerable groups, which were identified in this study as households with low income, poor financial circumstances and larger family size.
Keywords: D12; G50; E31; H55; 330; inflation; food insecurity; Central Asia; Caucasus; Southeast Asia; household survey; government aid